Nutritional and Non-Nutritional Factors Causing Anemia in Pregnant Women Globally: A Review - Evayanti, Arni (International Journal of Health Literacy and Science, 2025)
Anemia in pregnant women is a global health issue that has a significant impact on mothers and fetuses, especially in low- and middle-income countries. This condition can lead to premature birth, fetal growth disorders, and the risk of stunting. This study aims to analyze the nutritional and non-nutritional factors causing anemia in pregnant women globally and to recommend effective interventions. The method used was a literature review of national and international journals published between 2020 and 2025, with inclusion criteria and quantitative or qualitative methods. The results showed that the primary nutritional factors were iron, folate, and vitamin B12 deficiencies, exacerbated by low food intake and poor adherence to supplementation. Non-nutritional factors include socioeconomic status, education, age, infections (such as malaria and parasitic infections), chronic diseases, and limited access to healthcare services. Anemia is more common among adolescent pregnant women, those with low education levels, and those living in poverty. In conclusion, anemia in pregnant women is a multifactorial condition that requires a holistic approach through improved nutrition, health education, access to maternal services, infection control, and improved socioeconomic conditions. This approach aligns with WHO recommendations to reduce the global prevalence of anemia.